Evaluasi Konservasi Energi dan Air sebagai Aspek Program PBLHS pada Penerapan Konsep Green Building - Tavina Nilawati; Cynthia Permata Dewi; Mohammad Musthofa Al Ansyorie (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
The green building criteria of GBCI are an effort to maintain environmental stability. The concept of being environmentally friendly is applied by schools in the form of the PBLHS (Care and Culture for the Environment in Schools) program. The adiwiyata school used as the object of research is SDN Bareng 3. Green building assessment focuses on energy and water conservation, which are relevant for green building and the PBLHS program. This study aims to determine the percentage of energy and water conservation implementation in SDN Bareng 3, and compile recommendations to improve the application of green building according to the study aspect. The research method is descriptive quantitative guided by GREENSHIP Existing Building Version 1.1. The results shows that SDN Bareng 3 obtained a percentage of energy conservation application of 52.78%, and 15% for water conservation. The recommendations are to make energy and water efficient SOPs, make energy displays, use alternative energy, conduct laboratory tests on water quality, have a water recycling system, and use auto stop faucets